Textual Repetition as a Manifestation of Irony - Dalalyan, Manana (Armenian Folia Anglistika, 2015)
Text is a unit of language in use. It is a lexico-grammatical unit realized through a phonological system with its own hierarchy of units (Halliday 1977:6-7). Text has been defined as a communicative occurrence which meets seven standards of textuality – cohesion, coherence, intentionality, acceptability, informativity, situationality and intertextuality (Halliday, Hassan 1976:14-18). Application of repetition is also an important characteristic of a text. This particular study gives us a wide diapason to ascertain that repetitions on text level used by O. Wilde imply shades of comical meaning in general and ironical meaning in particular. The methodology underlies in the notion of irony asserted in the study of modality worked out by V. Vinogradov. The linguist suggests that there are two types of modality – objective and subjective. Objective modality mainly presupposes the author’s explicit evaluation of the surrounding world and events, thus revealing shades of humor. In the case of irony the utterance is performed through subjective modality which according to V. Vinogradov is the implicit subjective-evaluative attitude of the speaker/writer (Vinogradov 1950:725-731). Great is the number of studies, where repetition has been discussed on different linguistic levels. We will make an attempt to analyse it text level in Oscar Wilde’s fairy tale “The Devoted Friend” thus trying to prove that textual repetition implies shades of ironic modality in the fairy tale.
Keywords: textual repetition; modality; text linguistics; communicative context; impact